PENGARUH CITRA MEREK, HARGA DAN RELIGIUSITAS TERHADAP KEPUTUSAN PEMBELIAN LIPSTIK PADA MAHASISWI DI KOTA JAMBI - Ardilla Damayanti; Agustina Mutia; Laily Ifazah (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to determine the effect of brand image, price and religiosity on the decision to buy lipstick on female students in Jambi City. The population in this study were female students in Jambi City, namely Sulthan Thaha Saifuddin Jambi State Islamic University, Muhammadiyah University and Stai Ma'arif. The number of samples in this study were 371 people using a stratified random sampling technique. The method used in this study is the quantitative method, and the data analysis method used is validity test, reliability test, multiple linear regression, t test, f test and test the coefficient of determination with SPSS 25 tools. Based on the partial test results (T test) the brand image variable (X1) indicates that the calculated t value is greater than t table, namely 5.104 > 1.966 with a significance level of 0.000 <0.05, thus it can be concluded that